"What does development stand for?" A socio-semiotic conceptualisation. Issue 1 (1st January 2019) - Marais, Kobus
ABSTRACT: This paper argues for conceptualising development in terms of social semiotics. It points out that development studies is moving towards to human-centred rather than program-centred, technique-centred or engineer-centred thinking, that it has moved from a focus on technical transfer to dialogic interaction and that it has moved towards a postdevelopment imagination. On the basis of these moves, which all assume that development entails meaning-making, the article explores the contributions that biosemiotics and sociosemiotics can make towards conceptualising development. The article argues that semiotics provides development scholars with the conceptual tools to include both the material and the ideal in development thinking. It proposes a semiotic response theory of development in line with aspects of complexity thinking and semiotic realism.